Postural differences in turning kick vs back thrust kick among taekwon-do players: dominent leg - Mazlan, M. S. N.; Abu Osman, N. A.; Usman, J.; Wan Abas, W. A. B. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
There are many techniques in Taekwondo involving foots and hands. Through observations, athletes prefer to use techniques, which are easy to score and give more advantages of winning the game. In order to perform the quick movement, the body must rapidly adjust to the differences in posture to maintain a state of balance. Limited researches have been done on dynamic postural in Taekwondo. The purpose of this study is to determine the differences between the postural response to a turning kick (Dollyo Chagi) and back thrust kick (Dwit Chagi). To achieve the goal stated, 3D biomechanical analysis is done using kinematics approach. The parameters to be obtained are linear displacement of body centre of mass, kicking time duration and velocity of foot.